A statistical shape model of the tibia-fibula complex: sexual dimorphism and effects of age on reconstruction accuracy from anatomical landmarks. Issue 8 (11th June 2022) - Bruce, Olivia L.; Baggaley, Michael; Welte, Lauren; Rainbow, Michael J.; Edwards, W. Brent
Abstract: A statistical shape model was created for a young adult population and used to predict tibia and fibula geometries from bony landmarks. Reconstruction errors with respect to CT data were quantified and compared to isometric scaling. Shape differences existed between sexes. The statistical shape model estimated tibia-fibula geometries from landmarks with high accuracy (RMSE = 1.51-1.62 mm), improving upon isometric scaling (RMSE = 1.78 mm). Reconstruction errors increased when the model was applied to older adults (RMSE = 2.11-2.17 mm). Improvements in geometric accuracy with shape model reconstruction changed hamstring moment arms 25-35% (1.0-1.3 mm) in young adults.